Reducing Adjective Clauses into Participial Phrases: How Good Are The Students? - Noviani Noviani; Witri Oktavia (Universitas Negeri Padang, 2021)
Regarding that the ability to master clause and phrase construction affects the effectiveness and quality of the writing and reading, yet the studies about clause reduction are counted less in amount, it needs to be further examined. The objectives of this study are to find out the ability of English department students in reducing adjective clauses into participial phrases. The population of this research were 162 the second year English Department Students of Universitas Negeri Padang. The sample was 30 students chosen by using cluster sampling technique. Quantitative approach and descriptive method were used to analyze and describe the data which was gained from the test instrument. In general, the results show that averagely the students have such a fair level of mastery of the reduction of adjective clauses with average score 63.9. Indeed, specifically, they have good ability in changing the adjective clause to present, past or appositive and fair ability in correcting the errors. In addition, regarding the Arikunto’s standardized category, it was found that 33.3% students have good ability, and a couple of 20% students were categorized excellent and fair. In addition, 16.7% students were classified poor while 10% of them were noted fail.